The great American symphony [ music, the Depression, and war - Tawa, Nicholas E. (Indiana University Press, 2009)
Introduces the symphonists and their major works from the romanticism of Samuel Barber and the 'All-American' Roy Harris through the theatrics of Leonard Bernstein and Marc Blitzstein to the